Zastosowanie modeli hierarchicznych w bayesowskim wnioskowaniu statystycznym w przypadku niepełnych danych - Zmyślona, Beata (The Application of Bayesian Hierarchical Models in Statistical Inference in the Case of Incomplete Data, 2006)
In this paper we present the application of the Bayesian hierarchical models to analyse categorical data in the case of incomplete data sets. The Bayesian approach enables to use the knowledge about sample and missing data mechanisms. The main aim of using this approach is to improve statistical inference through the elimination of estimator bias and correct estimation of standard errors.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (17); 2006; nr 1123, s. 30-41